Assessing the reliability and validity of a shorter version of RIASEC in Turkish - Süerdem, Ahmet; Erkök, Bilge (My University, 2016)
Holland's RIASEC types are being frequently utilized in commercial vocational profiling tools for various human resources purposes. On the other hand, the length of the RIASEC scale and the copyright restrictions put by the publishers, are important barriers to application. In the present study, a RIASEC scale consisting of 41 items and adapted to Turkish language and culture, was developed. Each RIASEC type was represented with 6 or 7 items. Responses were obtained from a sample of 364 business professionals. Survey results indicated a good reliability for the scale, with a Cronbach's alpha of 0.889. However, reliability analysis pointed out to the need for revision of certain scale items when each RIASEC facet was separately analysed. Then, feedback regarding scale composition, wording and structure were gathered from 20 PhD students. Lastly, feedback of 7 HR professionals were sought, regarding scale items' expression and application of the scale in regular HR processes of companies. Results from face and content validity have been that for some items of the scale, more descriptive and specific expressions in Turkish are required. Moreover, some of the items would need to be reallocated to another facet where they would be more relevant. In line with findings from face and content validity, construct validity through confirmatory factor analysis also indicated that the short version of RIASEC must be revised substantially in order to become a valid tool for vocational profiling in Turkish context.
ERPA International Congresses on Education (ERPA) -- 42189
Keywords: RIASEC; work values; vocational interests; personality; job satisfaction; job performance; job turnover; validity; confirmatory factor analysis